THE VALUE OF MENTORSHIP IN FOSTERING SCIENTIFIC POTENTIAL AMONG UNDERGRADUATE DENTAL STUDENTS - Quispe-Salcedo, Angela (2025)
Many of us probably associate the terms “mentoring” or “mentorship” with the traditional teacher-student relationship that we experienced at school, or perhaps, to the relationship “boss-employee” at any organization. In any event, the term “mentoring” is generally acknowledged as the involvement of a person with more experience (the mentor), and a less experienced one (the mentee) that needs to be advised in specific areas. Mentoring relationships focus on helping the mentee’s growth and the accomplishment of his/her goals, including several approaches to doing so1,2. A more precise definition can describe mentoring as person-centered, long-term transformational process that requires the establishment of a trustful, respectful and confidential relationship between the mentor and mentee3.